Information Technology Management in Institutions - Huda Abdulhaleem Ibrahim (Scholars Digest Publishing, 2023)
The great role that modern information and communication technology has come to play in the lives of individuals, societies and economies has made it part of the infrastructure of many institutions that want to keep pace with modern developments, especially economic institutions that recognize the role of innovation and the effectiveness of innovations. Adapting to new inputs is inevitable, and Western institutions were the first in the field of introducing modern information and communication technology, and Algerian institutions were also not isolated from this development, as information and communication technology entered the core of their daily activities, and from this standpoint, this study directed us to go deeper. In the reality of the actual use of this technology in our institutions, we tried, within the framework of this study, to understand how information and communication technology contributes to the embodiment of effective time management in our institutions, because time management in the reality of the institution has become an urgent developmental necessity that can make the difference between institutions with new information technology. Our choice of this topic was not random, but rather the result of several reasons, both subjective and objective.
Keywords: Information; Technology Management; Institutions; communication.